2022
DOI: 10.3390/microorganisms10010125
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Clinical Oral Isolates of Actinomyces spp.

Abstract: Actinomyces species play an important role in the pathogenesis of oral diseases and infections. Susceptibility testing is not always routinely performed, and one may oversee a shift in resistance patterns. The aim of the study was to analyze the antimicrobial susceptibility of 100 well-identified clinical oral isolates of Actinomyces spp. against eight selected antimicrobial agents using the agar dilution (AD) and E-Test (ET) methods. We observed no to low resistance against penicillin, ampicillin-sulbactam, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Linezolid also displayed good coverage against Actinomyces spp., as reported by a study that analysed the antimicrobial susceptibility of 100 clinical oral isolates. No to low resistance (0-2%) was observed against penicillin, ampicillin/sulbactam, meropenem, clindamycin, linezolid, and tigecycline, while a high level of resistance to moxifloxacin occurred (>80%) [13]. Neuro-toxoplasmosis was also considered in the differential diagnosis, even though in our patient bradyzoites of Toxoplasma were not seen in the histological samples of brain biopsy and his serological test for IgG antibodies was negative.…”
Section: Case Discussion and Literature Reviewmentioning
confidence: 52%
“…Linezolid also displayed good coverage against Actinomyces spp., as reported by a study that analysed the antimicrobial susceptibility of 100 clinical oral isolates. No to low resistance (0-2%) was observed against penicillin, ampicillin/sulbactam, meropenem, clindamycin, linezolid, and tigecycline, while a high level of resistance to moxifloxacin occurred (>80%) [13]. Neuro-toxoplasmosis was also considered in the differential diagnosis, even though in our patient bradyzoites of Toxoplasma were not seen in the histological samples of brain biopsy and his serological test for IgG antibodies was negative.…”
Section: Case Discussion and Literature Reviewmentioning
confidence: 52%
“…It was concluded that actinomycosis infections are easy to manage using a first-line treatment powered by penicillin and amoxicillin [46]. Additional data confirmed the effectiveness of penicillin [47]. In cases of bacteremia, subjects were treated by β-lactam antibiotics or cephalosporins in periods of 3 days to 6 months [48].…”
Section: Discussionmentioning
confidence: 98%
“…respond very well to penicillin, and the risk of penicillin resistance is very minimal. [ 10 ] Therefore, considering the nonacid-fast nature of the microorganism, our patient was diagnosed as primary cutaneous actinomycosis and started on penicillin. The excellent response to penicillin supports our diagnosis.…”
Section: Discussionmentioning
confidence: 99%